“The Public Has The Right to be Protected From A Deadly Scourge”: Debating Quarantine, Migration and Liberal Governance during the 1847 Typhus Outbreak in Montreal - Horner, Dan (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2012)
During the summer of 1847 the impact of famine, disease, and social upheaval in Ireland was felt in port cities across the North Atlantic World. As an important hub of commerce and migration, Montreal was deeply affected by these events. The arrival of thousands of Irish migrants, many of whom had contracted typhus during their journey, touched off a contentious debate in the city. An engaged and alarmed public threw their support behind a proposal put forward by representatives of the municipal government that called for the construction of an elaborate quarantine facility just down the St. Lawrence River from the city. This facility, which migrants would be confined at until their healthy status was confirmed beyond reasonable doubt, promised to return order not only to Montreal, but to the entire migration process. The body appointed by the colonial administration, however, rejected the proposal, and tabled a far more modest plan that would continue to house migrants in sheds located just a stone’s throw away from the city’s western suburbs. The highly charged debate that ensued furnishes us with an opportunity to examine how the city’s political elite and the broader public were thinking through questions about migration, public health, and the contours of liberal governance. The objective of this article is to consider the role that moments of crisis such as this played in shaping the city’s political culture, and to place the events of 1847 in the context of the larger struggle between local and metropolitan authority occurring during this period.